Analisis Perbandingan Faktor Daya Pada Motor Kompressor Type Electromotor 15 KW - Juanda Mitra Situmeang; Mustofa Abi Hamid (Emitor: Jurnal Teknik Elektro, 2023)
This study analyzes the comparison of the power factor on the compressor motor type electromotor 15 kw (30 Bar/High pressure) at PT. Natural gas is a means of work. The power factor is the power losses generated by the electricity in the compressor motor, the power factor is also useful for limiting large power expenditures and the power factor or cos phi has a ratio between active power and apparent power. The results of this study indicate that the comparison of the power factor on the load of the 15 kw electromotor compressor motor at the initial start of the motor can be seen manually counting data and graphs every week. In the first week of total, 0.85 compared to the data for the second week, third week, and fourth week.